A nationwide family study of venous thromboembolism and risk of arterial vascular disease. Issue 16 (5th April 2016) - Zöller, Bengt; Li, Xinjun; Sundquist, Jan; Sundquist, Kristina
Abstract : Objective: This nationwide study aimed to determine whether venous thromboembolism (VTE) shares familial susceptibility with aortic aneurysm (AA), peripheral artery disease (PAD) and arterial thrombosis and embolisation (ATE) in locations other than the heart and brain. Methods: Nationwide Swedish family study. Data from the Swedish Multi-Generation Register for subjects aged 0–78 years old, covering the period 1964–2010, were linked to the Hospital Register. Familial risks (standardised incidence ratio, SIR) of AA, PAD and ATE were determined for individuals with a first-degree relative (parents/sibling) diagnosed with VTE. Separate analyses were done to determine risks for spouses. Results: A total of 13 063 individuals had AA, 15 494 had PAD and 7325 had ATE. Fully adjusted familial risks for individuals with family history (parent/sibling) of VTE were 1.04 (95% CI 1.00 to 1.08)) for AA, 1.42 (1.35 to 1.49) for ATE and 1.08 (1.04 to 1.13) for PAD. The familial sibling risks were 1.07 (0.99 to 1.14) for AA, 1.61 (1.48 to 1.74) for ATE and 1.19 (1.11 to 1.26) for PAD. Among individuals younger than 50 years of age, the familial risks were: 1.13 (0.99 to 1.29) for AA, 1.76 (1.62 to 1.91) for ATE and 1.12 (1.03 to 1.21) for PAD. In spouses of patients with VTE, the SIRs were 1.21 (1.17 to 1.25) for AA, 1.19 (1.14 to 1.23) for ATE and 1.26 (1.21 to 1.30) for PAD. Conclusions: VTE shares only weak familial susceptibility with AA and PAD in the Swedish population. However, ATE partially shares a moderate familial susceptibility and possibly genetic factors with VTE. Moreover, familial non-genetic factors may contribute to the observed familial associations.